(untitled) (Baghdad Science Journal, 2016)
The grain hardness, wet and dry gluten contents, protein and ash contents are determined in grains from different cultivars of wheat which are important in food products, either which are present in raw materials or in final products. Wheat is also a very important food raw material, and flour as the final product of milling. The importance of knowing the physical and chemical properties of wheat and flour is due to the determination of quality and kind of flour which is produced after the milling process. In this work, some physical and chemical properties of different wheat cultivars are determined and the comparisons of these characteristics are performed in both wheat and flour. Uruq Wheat sample (W5) has the highest results when compared with other wheat cultivar reaching 82 kg/ hectoliter, 9.2 % and 41 gm, 0.81, 8.8, 5.5, 30 %, 67 %, 73.6 %, 518, 858 specific weight, moister, 1000 grain Weight (gm), Ash %, Moister %, color test, moist. gluten %, Gluten index %, Absorption %, Falling No. and gelatination respectivelywith specifications grain white, transparent color, uneven gully depth and full cross-section of a glasses grain. The lowest results are by contrast with Forat cultivar in sample W2. Characteristics that are observed in this work are affect of the contents of with to moister, ash, protein, gluten and water absorption values there are useful for milling industry of different wheat cultivars.